Chemotherapy in hormone-sensitive metastatic prostate cancer: Evidences and uncertainties from the literature. (April 2017) - Gravis, Gwenaëlle; Audenet, François; Irani, Jacques; Timsit, Marc-Olivier; Barthelemy, Philippe; Beuzeboc, Philippe; Fléchon, Aude; Linassier, Claude; Oudard, Stéphane; Rebillard, Xavier; Richaud, Pierre; Rouprêt, Morgan; et al.
Highlights: Addition of docetaxel to androgen-deprivation therapy should be the new standard of care for men newly diagnosed with metastatic prostate cancer. Discriminating factors to identify the best candidates to chemotherapy, like the volume of metastases, need to be validated. The role of docetaxel in earlier stage of the disease is under investigation. Abstract: Data from the literature support with strong evidence the addition of docetaxel to androgen-deprivation therapy (ADT) for men with metastatic prostate cancer, and starting therapy for the first time. A meta-analysis of three randomized controlled trials showed a significant improvement of overall survival when ADT was combined with docetaxel when compared to ADT alone (HR = 0.77; 95% CI: 0.68–0.87; p < 0.0001). Consequently, combination therapy should be considered presently as the new standard of care, using 6 cycles of docetaxel, without prednisone. However, candidates for this upfront combination therapy in whom the balance between its side effects and benefits is favorable are still to be identified more precisely. Patients' stratification according to Gleason score, previous local treatment and age or performance status were shown to have a prognostic impact. The volume of metastases, as defined in the CHAARTED study for instance, could be an interesting predictive factor. However, data accumulated until now remain only hypothesis generating and further analysis and studies are needed to establish any potential discriminating factors. Several new efficient therapeutic options are now available in prostate cancer management and should be evaluated against a chemo-hormonal combination therapy. Other trials are warranted to establish the role of docetaxel in earlier stages of the disease, the combination with the new hormonal therapies as well as the best management options after docetaxel.